Análisis de la cinética del secado de cacao en función de la temperatura. - Carguachi Caizatoa, Jose Bolívar (2023)
Cocoa is a product highly required by the international market; Many are the investments made in research and development, to obtain new products, but very few investigations focus on the kinetics of cocoa drying. The treatment of cocoa is a process that takes time and effort, for this reason there is a need to carry out processes that allow it to accelerate its drying, meeting quality standards, so that it can be placed on the market quickly. The objective of the study is to obtain the variables of the mathematical models of drying kinetics of national cocoa as a function of temperature in a controlled regime, through an experimental and mathematical approach.